(untitled) (Research, Society and Development, 2025)
The COVID-19 pandemic has had profound impacts on global health, including the emergence of persistent complications affecting various body systems even after recovery from the acute infection.This study aims to investigate the respiratory, cardiovascular, neurological, and psychological sequelae resulting from COVID-19 infection, with an emphasis on recent data and studies regarding the long-term impacts on patients’ health. It is a literature review based on scientific articles from different authors, discussing the persistent complications of COVID-19 regardless of the severity of the initial infection. The research was conducted through the analysis of selected articles from the Google Scholar and SciELO databases, focusing on the main post-COVID-19 clinical manifestations and describing the most common sequelae found in patients after recovery from the acute phase of the disease. As results, various debilitating conditions were observed, such as respiratory difficulties, arrhythmias, central nervous system injuries, and psychiatric and cognitive disorders. Respiratory sequelae, for example, affected patients’ functional capacity, impairing daily activities, while cardiovascular complications increased the risk of heart disease. Additionally, neurological sequelae, such as headaches and cognitive impairment, and psychological symptoms, including anxiety and depression, showed a significant impact on patients’ quality of life. In conclusion, the study highlights the complexity of post-COVID-19 Syndrome and the need for long-term follow-up to mitigate the effects of these sequelae, while also emphasizing the importance of future research to understand the extent of these conditions and develop effective interventions.